Tahapan Kegiatan pada Proses Penggarapan Karya Musik di Studio Markas Kota Prabumulih - Winanda, Tiara; Heryanto, A; Hidayatullah, Fadhilah (Institut Teknologi Pendidikan Indonesia, 2022)
The purpose of this study was to find out how the stages of activity in the process of composing a piece of music at the Prabumulih city headquarters studio, the method used inthis research is a qualitative descriptive method. The informants in this study were Kak Budiand his students. The object of this research lies in the stages or steps used during the process of composing a piece of music that was worked on in the Prabumulih city headquarters studio. Collecting data in this study using observation techniques, interviews, and documentation. The data analysis technique used is qualitative data analysis, namely in the form of data collection, data reduction, data presentation, and data verification. Based on the results of the study, it can be concluded that, from data analysis, it can be seen that there are 6 stages or steps in the process of composing a musical work at the Prabumulih city headquarters studio. has gone through the stages or steps that have been determined.